Modern Gnostics: The Pursuit of the Sacred in Indonesian Islam - Joel S. Kahn (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
This paper reports on an ongoing research project on “New Southeast Asian Spiritualties” and offers a preliminary analysis of new Muslim religiosities in the Jakarta metropolitan area (Jabodetabek). Most of the analyses of the processes of “Islamization” in places like Indonesia and Malaysia in the last few decades focus on a particular set of social cum political agendas: the imposition of sharia law, the Islamization of the state apparatus, the increased emphasis on the external markers of ‘Islamic identity’ and the like. Yet, there appears to be an equally significant, even sometimes opposing, tendency among Southeast Asian Muslims that involves them in seeking out more intense and personalised ‘inner’ forms of religious experience, a process with parallels elsewhere in the world. In the paper, I discuss examples of this tendency based on fieldwork in the greater Jakarta area, and ask about its implications for current understandings of the consequences (for democracy, secularism, human rights, gender relations, etc.) of Islamization in Southeast Asia.